THE FIRST OBSERVATION OF THE BANK MYNA ACRIDOTHERES GINGINIANUS (LATHAM, 1790) (FAMILY: STURNIDAE, CLASS: AVES) IN THE WILD IN IRAQ - Salwan Ali Abed; Mudhafar A. Salim (Al-Qadisiyah Journal of Pure Science, 2019)
The Bank Myna Acridotheres ginginianus (Latham, 1790) is a member of the Acridotheres Genus of the Family Sturnidae (Passeriformes). This species spreads within the northern parts of South Asia around or close to the human settlements with recent expanding towards southern India. It can be distinguished from its analogous Common Myna Acridotheres tristis of the same Genus, which has been observed for the first time in Iraq at 1997, mainly by the orange skin patch around the eye with some other key morphological features. Since it was observed for the first time in Iraq in the bird-markets at 2001, some individuals of Bank Myna have been occasionally found in the cages in five districts. The first records for this species in the wild in Iraq were represented by unconfirmed observations in the wild at 2005 and 2008 due to the lack of documentation. This paper documents the first confirmed observation of the Bank Myna Acridotheres ginginianus for Iraq.